Three-dimensional kinematics of the trunk, pelvis, hip, and knee during the single-leg squat and hip torque in subjects with isolated patellofemoral osteoarthritis compared to individually matched controls: Preliminary results - Cristiano Carvalho,; Fábio Viadanna Serrão,; Adalberto Felipe Martinez,; Paula Regina Mendes Da Silva Serrão, (Archives of Rheumatology, 2024)
Objectives: This study aimed to compare three-dimensional kinematic of the trunk, pelvis, hip, and knee during the single-leg squat and hip torque in individuals with and without isolated patellofemoral osteoarthritis (PFOA). Patients and methods: This cross-sectional study evaluated trunk, pelvis, hip, and knee kinematics at 30°, 45°, and 60° knee flexion during the single-leg squat using the Vicon motion capture and analysis system, the Nexus System 2.1.1, and 3D Motion Monitor software. Sixteen individuals (8 males, 8 females; mean age: 49.3±6.2 years; range 40 to 61 years) participated in the study, of which eight were PFOA patients and eight were healthy controls. Isometric hip abductor, extensor, and external rotator torques were evaluated using a handheld dynamometer. Results: The PFOA group exhibited greater hip adduction at 30° (p=0.008), 45° (p=0.005), and 60° (p=0.008) knee flexion in the descending phase of the single-leg squat, as well as at 60° (p=0.009) and 45° (p=0.03) knee flexion in the ascending phase. No significant differences were found between groups for other kinematic variables (p>0.05). The PFOA group exhibited lower isometric hip abductor (p=0.02), extensor (p< 0.001), and external rotator (p=0.007) torques. Conclusion: Individuals with PFOA exhibited excessive hip adduction that could increase stress on the lateral patellofemoral joint at 30°, 45°, and 60° knee flexion during the single-leg squat and exhibited weakness of the hip abductors, extensors, and external rotators in comparison to healthy controls.